LGBT Moral Injury Scale: Initial Validation and Preliminary Psychometric Properties - González-Rivera, Juan Aníbal (2026)
Background: Moral injury has been linked to guilt, shame, self-condemnation, and moral disorientation; however, existing measures have been developed primarily in military, veteran, or healthcare contexts and may not adequately capture identity-related moral suffering in LGBTQ+ populations. Objective: To develop the LGBT Moral Injury Scale (LGBT-MIS) and provide initial psychometric evidence for its use with LGBTQ+ adults in Puerto Rico. Method: A total of 242 LGBTQ+ adults were recruited through social media and snowball sampling. Because multivariate normality was violated, we conducted confirmatory factor analyses using robust estimation to compare a unidimensional model, a theory-driven five-factor model, and refined alternative models. We evaluated global model fit, factor loadings, item discrimination, internal consistency (α, ω, and composite reliability), convergent validity (AVE), discriminant validity (ASV, MSV), interfactor correlations, and external convergent associations with PTSD symptoms and Negative Religious Coping. Results: The unidimensional model showed poor fit, whereas the theory-driven model demonstrated mixed fit and several loadings below .65. After item refinement, a 15-item, five-factor solution—Guilt, Shame, Moral Conflicts, Religious Struggle, and Self-Condemnation—showed adequate fit, satisfactory reliability, and acceptable item discrimination. AVE supported convergent validity, and ASV supported discriminant validity; however, MSV exceeded AVE for Guilt, Shame, and Moral Conflicts, indicating partial overlap among these factors. Interfactor correlations were positive and moderate. Associations with PTSD symptoms and Negative Religious Coping provided initial evidence of external convergent validity. Conclusions: The LGBT-MIS provides promising initial support as a multidimensional measure of moral injury in Puerto Rican LGBTQ+ adults. With further validation, the scale may support research and clinically informed assessment of guilt, shame, moral conflict, religious struggle, and self-condemnation in LGBTQ+ populations.